A life skills development programme for youth football coaches: Programme development and preliminary evaluation - Bowley, C.; Cropley, B.; Neil, R.; Hanton, S.; Mitchell, I. (Sport & Exercise Psychology Review, 2018)
The Manuscript presents two linked studies that together aimed to design, deliver, and evaluate a service-user informed education programme that focused on improving coaches` understanding of, and ability to facilitate, life skill development through grassroots football in the UK. First, focus groups (n = 14) were conducted with key stakeholders (n = 56) to explore their perceptions of life skills and how they might be developed within grassroots football. The findings revealed six life skill themes, with social skills emerging as the most pertinent for the context. Further, the role of the coach in formally faciliting life skill development was expressed, suggesting that they are not developed implicitly through sport participation alone. Second, using the findings from study one, a coach education programme was designed and subsequently delivered to a total of 45 coaches. Preliminary evaluation, using a triangulation of sources, revealed that the programme was successful in developing participants` knowledge and understanding of life skills as well as improving their competence and confidence to integrate life skill development into their coaching practice. Support is, therefore, offered for the development of context specific life skill development programmes that are based on key stakeholder needs and expectations.